Espécies arbóreas de Papilionoideae (Leguminosae) na região noroeste do estado de São Paulo, Brasil - Martins, Milena Ventrichi; Cavassan, Osmar; Tozzi, Ana Maria Goulart De Azevedo; Koch, Ingrid (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2016)
In this study, we collected woody plants of Papilionoideae, Leguminosae, in the northwest region of São Paulo state, southeastern Brazil. The study area has one of the most fragmented vegetation within the context of the region, and it is still poorly known about the flora. Nineteen species were recorded in eleven genera and three tribes. The most representative tribes were Sophoreae, with the genus Bowdichia, Leptolobium, Myroxylon, Sweetia and Ormosia; tribe Dalbergieae, with Andira, Centrolobium, Machaerium and Platypodium, and tribe Dipterygeae represented by Dipteryx and Pterodon. Machaerium presented the highest number of species, with eight, followed by Leptolobium, with two species. The other genera were represented by one species each. The species distribution data showed that the regional flora consists of species with wide distribution in the Cerrado, in central Brazil, and species that occur primarily in the Atlantic forest in eastern Brazil. Keys, descriptions and illustrations of the taxa found are displayed.

Neste estudo foram coletados os indivíduos arbóreos e arbustivos da subfamília Papilionoideae na região noroeste do estado de São Paulo, Sudeste do Brasil. A área possui a vegetação mais fragmentada do Estado e é ainda pouco conhecida quanto à composição da flora. Foram registradas 19 espécies arbóreas de Papilionoideae reunidas em 11 gêneros e três tribos. As tribos mais representativas foram Sophoreae, com Bowdichia, Leptolobium, Myroxylon, Ormosia e Sweetia, e Dalbergieae com Andira, Centrolobium, Machaerium e Platypodium, enquanto Dipterygeae foi representada por Dipteryx e Pterodon. O gênero com maior número de espécies foi Machaerium, com oito, seguido por Leptolobium, com duas. Os demais gêneros foram representados por uma espécie cada. Os dados de distribuição das espécies apontam para uma flora regional composta por espécies com ampla distribuição no domínio Cerrado, do Brasil central, e espécies que ocorrem prioritariamente no domínio de Mata Atlântica, no Brasil oriental. Chaves para identificação, descrições e ilustrações dos táxons encontrados são apresentadas.
Tree species of Papilionoideae (Leguminosae) in northwest of São Paulo state, Brazil
Keywords: Fabaceae; Faboideae; Cerrado; Semideciduous Forest; floristic; Fabaceae; Faboideae; Cerrado; Floresta Estacional Semidecidual; florística